Faktor-Faktor yang Mempengaruhi Indeks Pembangunan Manusia (IPM) Provinsi Sumatera Barat dengan Menggunakan Analisis Regresi Data Panel - Silvia Fransiska; Yusmet Rizal (UNIVERSITAS NEGERI PADANG, 2020)
Abstrak— The Human Development Index (HDI) is a parameter that functions to assess the success of the quality of human life. The increase in HDI in West Sumatra Province was not accompanied by an equal distribution of HDI in each Regency / City. The factors used in the study are poverty, life expectancy (AHH), average school length (RLS), long school expectancy (HLS), per capita expenditure and economic growth. The research was conducted to see what factors influenced HDI in West Sumatra Province from 2012 to 2018, in which districts / cities were divided into three regional groups based on regional profiles, regional potential and average regional income. The results showed that AHH, RLS, HLS and per capita expenditure were factors that influenced HDI for group I regions. Poverty, HLS and expenditure per capita were factors that influenced the HDI of group II regions. Keywords: HDI, Panel Data Regression Analysis, Fixed Effect Model (FEM).